HIGH STEP-UP SWITCHED Z-SOURCE DC-DC CONVERTER WITH MINIMAL COMPONENTS COUNT - KUMAR, RAHUL (2021)
Fuel cells or photovoltaic panels offer low output voltage, and it is essential to boost this voltage before connecting to the grid or an inverter.